The study of earthworms diversity in UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah, Negeri Sembilan / Norainmuni Hamid - Hamid, Norainmuni (Faculty of Applied Sciences, 2017)
The study of earthworms diversity was be done in UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah. UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah is nearby to the forest reserve and it is considered as Tropical Rainforest which has the humid climate and has the higher potential for the abundance of the earthworms to live. Unfortunately, there is lack of study about the population of earthworms in UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah. Thus, this study that being done is to provide more data and information about the diversity of the earthworms exists in UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah. The present study was carried out during March until April of 2017 at the small part in UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah focusing about the diversity of the earthworms. The earthworms were collected using hand sorting method and being preserve with 10% diluted formalin solution. For six day being sampling, only 119 individuals were being found. 114 individuals is contribute by the Pontoscolex corethurus and the other 5 individuals is comes from Amynthas gracilis. The value for the Shannon Diversity Index (H') is 0.17 while the value for Evenness Index (E) is 0.25. The value of Richness Index (D) is 0.20. All of the index shows that the habitat is low in diversity and dominated by the presence of Pontoscolex corethurus.